Operational Risk Management and the Case of Albania - Beja, Anjeza (European Journal of Multidisciplinary Studies, 2016)
Starting 1999, when operational risk was instroduced for the first time as part of pillar 1 minimum regulatory capital charge, supervisors and the banking industry recognized the importance of such risk in evaluating the risk profiles of financial institutions. The increasing use of automated technology, the growth of e-commerce and the expansion of activity ect. , create increased operational risk, and expose the institution to possible losses. Such risk has been introduced in the regulatory framework of Bank of Albania in 2011 and since then, there have been positive developments in the consideration of this risk from the supervisory point of view. The regulation included qualitative criteria for the identification and monitoring of operational risk, whereas the quantitative measurement of capital charge for operational risk has been introduced through the implementation of capital adequacy ratio regulation based in Basel 2.